Maxillary Complete Denture Outcomes: A Systematic Review of Patient-Based Outcomes - Thalji, Ghadeer; McGraw, Kate; Cooper, Lyndon F (The International journal of oral and maxillofacial implants, 2016)
The aim of this systematic review is to report on the current knowledge regarding patient satisfaction as a primary outcome for maxillary complete denture therapy. We asked, "For the maxillary edentulous patient treated using maxillary dentures, what are the patient-based outcomes regarding quality of life and treatment satisfaction." An electronic search of publications up to March 2014 was established using four databases: PubMed, Web of Science, Scopus, and Embase. To meet the ultimate goal of establishing clinical guidelines based on available information, prospective comparative studies, cohort prospective studies, and retrospective studies on more than 10 subjects were included. The electronic search identified 4,530 articles that were evaluated at the title, abstract, and article level to include 31 articles of interest. The patient-based outcomes and satisfaction data included were examined and reported. The studies included 5,485 participants. Of these, 2,685 were identified as wearing maxillary complete dentures. Reported mean ages ranged from 59.7 to 73.6 years. A systematic review indicated that the provision of new maxillary complete dentures for edentulous patients results in improved self-reported satisfaction and oral health-related quality of life. The included reports, while providing evidence that complete denture satisfaction of participants and new dentures improve self-reported outcomes, did not include variables that influence these positive outcomes. A broad range of evidence supports the use of complete dentures for rehabilitation of the edentulous maxilla. When considering treatment of the edentulous maxilla, the expectations of patients for esthetic and phonetic (social) rehabilitation are high and can be met using maxillary complete dentures as the mode of prosthetic rehabilitation. Patients dissatisfied with new complete dentures may be referred for dental implant therapies involving fixed or removable prostheses.